Adhesion enhancement and amine reduction using film redeposited at the interface of a stack of plasma-enhanced CVD dielectrics for Cu/low-k interconnects. (23rd January 2019) - Miyajima, Hideshi; Watanabe, Kei; Ishikawa, Kenji; Sekine, Makoto; Hori, Masaru
Abstract: The dielectric interface for a stack of SiOC and SiCN films in Cu/low- k interconnects is engineered using Ar plasma pretreatment of the top surface of SiCN, which prevents oxidization during SiOC film deposition. Oxidized SiCN causes delamination of the SiOC film and resist poisoning through amines generated during resist baking, which can lead to undeveloped photoresist. The Ar plasma pretreatment in the plasma-enhanced chemical vapor deposition chamber modifies the interface by redepositing a thin pre-coated SiOC film from the upper electrode surface. This redeposited SiOC film acts as a buffer for oxygen plasma during SiOC film deposition.